Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates. Issue 11 (25th September 2020) - Tillmann, W.; Hagen, L.; Garthe, K.‐U.; Hoyer, K.‐P.; Schaper, M.
Abstract: Numerous studies already identified that the fatigue strength of 316 L parts processed by laser beam melting (LBM) is distinctly affected by the surface integrity. Among others, surface defects as well as residual stresses are of crucial importance. Despite new findings in the field of surface engineering of laser beam melting (LBM) parts, the low cycle fatigue strength of thermally sprayed additively manufactured substrates has not been in the focus of research to date. This study aims at evaluating the effect of different pre‐treatments onto 316 L substrates processed by laser beam melting (LBM) prior to the deposition of a high velocity oxy‐fuel (HVOF) sprayed tungsten carbide‐cobalt coating and their effect on the low cycle fatigue strength. Therefore, 316 L substrates were examined in their as‐built state as well as after grit blasting with regards to the surface roughness, strain hardening effects, and residual stresses. To differentiate between topographical effects and residual stress related phenomena, stress‐relieved 316 L substrates served as reference throughout the investigations. The tungsten carbide‐cobalt coated and differently pre‐treated 316 L substrates were mechanically tested under quasi‐static and dynamic load conditions. Besides the low cycle fatigue strength, the fracture toughness as well as the fracture mechanism were identified based on fracture surface analysis. Abstract : This study aims at evaluating the correlation between the effect of different substrate surface conditions (i. e. grit blasted, as‐built) and the fatigue strength of the produced tungsten carbide‐cobalt coated 316 L additive manufactured substrate composites under quasi‐static and dynamic load conditions.